Synchronous colonic malignancy and tuberculosis: a rare histologic surprise - Khemchand, Agrawal Kavita; Singh, Kaptan; Vaiphei, Kim; Kaman, Lileshwar (International Surgery Journal, 2020)
Coexistence of colorectal cancer and tuberculosis of same site is described in few of case reports. Tuberculosis (TB) is known to involve any part of the body. Intestinal TB accounts for the majority of extra pulmonary TB, ileocecal region being the most common site. TB has been known to be associated with various types of malignancy. The most common association is malignancy and pulmonary TB. However, association of extra pulmonary TB and malignancy at the same site is relatively uncommon. This case report describes synchronous colonic malignancy and tuberculosis on histopathological evaluation of the resected specimen in a 42-year female patient.